Enhancing community health sustainability through the use of Maqasid Al-Shariah theory - Haque, A. K. M. Ahasanul; Abd Manaf, Noor Hazilah; Uddin, Md Nazim; Akther, Naznin; Mokhtar, Aida (Inderscience Publishers, 2024)
Abstract: Sustainable community health (SCH) is a new hospital administration and service paradigm incorporating Maqasid al-Shariah. Medical advice often contradicts Maqasid al-Shariah. This study investigates the requirements for a Maqasid al-Shariah-based community health system, particularly in administration and treatment. This qualitative study includes expert interviews and a literature review. This lengthy study seeks to expand the understanding of Maqasid al-Shariah-based SCH components. Preliminary analyses show that a Shariah Advisory Council and Critical Points are necessary for community health. The Shariah Advisory Council links healthcare practices to Maqasid al-Shariah, ensuring ethical and moral treatment – Shariah Critical Points show where Maqasid al-Shariah can be weakened or neglected, allowing targeted interventions and improvements. This research explores the reasons and conditions for creating methodologies for measuring hospital Maqasid al-Shariah adherence. This study can help healthcare institutions implement Maqasid al-Shariah for more sustainable and community-centred care. This research addresses Maqasid al-Shariah-based community health system requirements. Maqasid al-Shariah’s hospital administration and treatment work shows the organisational structure and necessary components for community health. This research can assist healthcare institutions in implementing Maqasid al-Shariah procedures and promoting ethical, socially responsible, and sustainable healthcare.